2016
DOI: 10.1007/s12012-016-9370-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic and Pro-survival Effects of Food Restriction on High-Fat Diet-Induced Obese Hearts

Abstract: Food restriction and weight loss are known to prevent obesity-related heart diseases. This study investigates whether food restriction elicits anti-apoptotic and pro-survival effects on high-fat diet-induced obese hearts. Histopathological analysis, TUNEL assay, and Western blotting were performed on the excised hearts from three groups of Sprague-Dawley rats which were fed with regular chow diet (CON, 13.5 % fat), a high-fat ad libitum diet (HFa, 45 % fat), or a high-fat food-restricted diet (HFr, 45 % fat, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Based on CR experimen cytokine, chemokine, and metabolic pathways are significantly regulated by CR the aging process. It is expected that a better understanding of senoinflam mechanisms will provide a basis for the discovery of molecular targets that modulate age-related chronic inflammatory conditions and enable the develop effective interventions to delay aging and prevent the occurrence of aging-assoc ├ Human, Mouse, Rat [74,82,[246][247][248] IGFBP2 ↑ Human TCGA data base Metabolism Insulin resistance ↑ [209] and activation of AMPK [215,216] and antioxidant genes [209]. K neuroprotective and lifespan extension effects similar to CR in C. elegans [21 transcription of antioxidant genes, including manganese superoxide dismu FOXO3, both of which exert antioxidant effects [209].…”
Section: Discussionmentioning
confidence: 99%
“…Based on CR experimen cytokine, chemokine, and metabolic pathways are significantly regulated by CR the aging process. It is expected that a better understanding of senoinflam mechanisms will provide a basis for the discovery of molecular targets that modulate age-related chronic inflammatory conditions and enable the develop effective interventions to delay aging and prevent the occurrence of aging-assoc ├ Human, Mouse, Rat [74,82,[246][247][248] IGFBP2 ↑ Human TCGA data base Metabolism Insulin resistance ↑ [209] and activation of AMPK [215,216] and antioxidant genes [209]. K neuroprotective and lifespan extension effects similar to CR in C. elegans [21 transcription of antioxidant genes, including manganese superoxide dismu FOXO3, both of which exert antioxidant effects [209].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that women became overweight or obese after menopause and, consequently, many health risks are increased [42]. Obesity or weight gain may lead to cardiac apoptosis [43,44,45,46], but it is still unclear whether the increased cardiac apoptotic activity is partially due to the deleterious factor of weight gain after an ovariectomy. Moreover, the coexistence and independence of ovariectomy and hypertension share many of the same or different disease processes and risk factors, such as weight change [42], increased inflammation [47], oxidative stress [48,49], renin-angiotensin system activity [6,26] and heart and renal changes [50].…”
Section: Discussionmentioning
confidence: 99%
“…Weight gain or Obesity may also lead to cardiac widely dispersed apoptosis. However it is still unclear whether the increased cardiac apoptotic activity is partially due to the deleterious factor of weight gain after ovariectomy [3941]. Nevertheless, in our current study, we show that body weight can be partially decreased when combined with 17β-estradiol and exercise training, and even diminished cardiac apoptotic activity after an ovariectomy.…”
Section: Discussionmentioning
confidence: 38%